The road to a transcultural America: the case of American Muslim girls - Kabir, Nahid Afrose (BRAC University, 2019)
This article was published in the Journal of Intercultural Studies [© 2016 Published by Routledge] and the definite version is available at http://doi.org/10.1080/07256868.2016.1163532 The Article's website is at https://www.tandfonline.com/doi/full/10.1080/07256868.2016.1163532